Diagnostic utility of the Minnesota multiphasic personality inventory-2 in patients diagnosed with psychogenic non-epileptic seizures in the Czech Republic - Krámská, Lenka; Myers, Lorna; Hrešková, Lucia; Krámský, David; Vojtěch, Zdeněk (Epilepsy & behavior, 2021)
PURPOSE: The purpose of the present study is to examine the Minnesota Multiphasic Personality Inventory 2 (MMPI-2) scores of individuals diagnosed with psychogenic non-epileptic seizures (PNES) in a tertiary epilepsy center in the Czech Republic. METHOD: Patients (F:M 130:45; mean age 36.8 years; 12.7 years of education, frequency of seizures 0.37 per day, illness duration 5.75 years) were assessed while inpatients at the Epilepsy Center, Na Homolce Hospital, Prague. Patients underwent video-EEG testing and comprehensive neuropsychological testing and personality assessment which included the MMPI-2. RESULTS: Elevated (+1.5SD) F and Back F (Fb) validity scales were observed along with elevated clinical scales Hypochondriasis (Hs), Depression (D), Hysteria (Hy), Psychasthenia (Pt), and Schizophrenia (Sc). Scores higher than 1 SD were found in Psychopathic Deviate (Pd), Paranoia (Pa), Hypomania (Ma) andSocial Introversion (Si) scales and on validity scales True Response Inconsistency Scale (TRIN) and Variable Response Inconsistency Scale (VRIN). CONCLUSION: Patients diagnosed with PNES exhibit numerous elevations on the MMPI-2. Understanding the underlying psychological constructs of the patient with PNES more accurately improves predictive utility (for the presence of PNES) and allows the clinician to offer interventions that are more customized. Minnesota Multiphasic Personality Inventory results may be useful to exclude other possible diagnoses and to further determine the individual's characteristics that may be helpful when tailoring treatment, including psychotherapy.
Keywords: dospělí; Epilepsy; Seizures; záchvaty; Adult; Psychogenic non-epileptic seizures; konverzní poruchy; Dissociative seizures; lidé; MMPI; Personality Inventory; Minnesota Multiphasic Personality Inventory-2 (MMPI-2); epilepsie; Czech Republic; Personality assessment; Česká republika; osobnostní dotazník; Neuropsychology; Conversion Disorder; Humans